Effects of physical activity on regulatory emotional self-efficacy, resilience, and emotional intelligence of nurses during the COVID-19 pandemic - Wu, Ruoshan; Jing, Longjun; Liu, Yang; Wang, Huilin; Yang, Jingyu (Frontiers in Psychology, 2022)
The normalization of epidemic prevention and control has exacerbated nurses’ physical and mental stresses. The important role of physical activity in relieving nurses’ physical and mental stresses has received extensive attention from researchers in recent years. The purpose of this study was to investigate the influence of physical activity on the regulatory emotional self-efficacy, resilience, and emotional intelligence of nurses and explain their interactions. The present study adopted the cluster sampling method. From April to May 2022, a total of 500 nurses in six municipal hospitals in Changsha City were selected. Finally, 402 valid data samples were obtained. Afterwards, AMOS 23.0 (by maximum likelihood estimation) was used to process the collected data and analyze the proposed hypotheses by using 5,000 bootstrap samples to test the mediating effects of the structural equation model. The results demonstrated that nurses with higher levels of physical activity have a higher emotional regulation self-efficacy, emotional intelligence, and psychological resilience. The positive influence of physical activity on emotional regulation self-efficacy is completely mediated by emotional intelligence and resilience, and this explanatory power is far higher than any previous study (R2 = 0.49). The positive emotions generated by an individual’s physical activity have an important explanatory role for individuals who want to establish more emotional regulation self-efficacy, emotional intelligence, and psychological resilience.